2018
DOI: 10.1186/s13071-017-2580-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between egg- and antigen-based diagnostics of Schistosoma mansoni infection pre- and post-treatment in Uganda

Abstract: BackgroundSchistosomiasis is a major socio-economic and public health problem in many sub-Saharan African countries. After large mass drug administration (MDA) campaigns, prevalence of infection rapidly returns to pre-treatment levels. The traditional egg-based diagnostic for schistosome infections, Kato-Katz, is being substituted in many settings by circulating antigen recognition-based diagnostics, usually the point-of-care circulating cathodic antigen test (CCA). The relationship between these diagnostics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Other studies suggest slightly lower or even much higher percentages. 12 , 37 Sensitivity and specificity estimates for POC-CCA in Leiden were among the highest above 90%, only specificity for the trace negative model was 86%. Unfortunately, sensitivity and specificity changed in the wrong direction with the transition from trace considered negative to trace considered positive.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies suggest slightly lower or even much higher percentages. 12 , 37 Sensitivity and specificity estimates for POC-CCA in Leiden were among the highest above 90%, only specificity for the trace negative model was 86%. Unfortunately, sensitivity and specificity changed in the wrong direction with the transition from trace considered negative to trace considered positive.…”
Section: Discussionmentioning
confidence: 96%
“…This result revealed that the POC-CCA test detects more infected individuals when “trace” results are classified as positive results, as also described by Prada et al . 2018 26 . In contrast, when “trace” results were considered negative, the POC-CCA test showed better performance in the detection of true negative results.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between prevalence and mean intensity of infection is non-linear with the precise relationship depending on the degree of parasite aggregation in the human host population as measured inversely by the negative binomial aggregation parameter (k) [ 6 , 41 43 ]. Following treatment, prevalence typically bounces-back but at a lower intensity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common diagnostic tools for schistosomiasis are the traditional Kato-Katz diagnostic technique (which current WHO guidelines are based on [ 2 ]) and the relatively newer, more sensitive point-of-care circulating cathodic antigen test (CCA) diagnostic test [ 37 , 44 , 45 ]. Although Kato-Katz is seen as the cheaper test, given the increased sensitivity of CCA, this may outweigh costs in long term as the CCA test is faster, less labour intensive and likely to have a higher prevalence threshold [ 14 , 37 , 46 ]. However, the costs vary in different settings and costs per test are not constant [ 14 ].…”
Section: Discussionmentioning
confidence: 99%